EDUKASI BIJAK BERMEDIA SOSIAL: UPAYA PENCEGAHAN DAMPAK NEGATIF PADA SISWA SDN 13 BUNOBOGU DESA LONU - Nurjanah A. Habir; Kofifa Indar Furwansa; Sahuria Fitri; Triyuniari Liputo; Nasriani (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
According to several recent studies, many children are included in the category of addiction to using cellphones, especially the use of social media. Increasingly with the degree of addiction the lightest or the most severe. Community service activities carried out by the service team reported in this study will specifically focus on socializing the dangers of using social media. Social media was chosen because the risks and dangers are greater for children because of the nature of online communities that do not interact directly and anonymously. The method used in this community service activity is active participation, which in this activity uses 4 methods, namely implementation, problem solving and games